Nitrogen-doped carbon dots as a fluorescence probe suitable for sensing Fe3+ under acidic conditions. (3rd November 2016) - Li, Guangming; Lv, Nan; Bi, Wenzhi; Zhang, Jilin; Ni, Jiazuan
Abstract : The N-CDs with primary amines and catechol groups on the surface serve as a fluorescence probe for sensing Fe 3+ at low pH. Abstract : To obtain nitrogen-doped carbon dots (N-CDs) for sensing Fe 3+ under acidic conditions, robust and highly fluorescent N-CDs were prepared by one-pot hydrothermal treatment of dopamine and ethylenediamine. The N-CDs have a relatively uniform size of approximately 4.9 nm and good water dispersibility. The N-CDs exhibit strong visible fluorescence ( ca. 497 nm) and high stability at low pH ( i.e. 2–3). The FTIR spectra and the XPS analyses indicated that primary amines and distinctive catechol groups exist on the surface of the N-CDs. The FTIR spectra further prove that the catechol groups on their surfaces can be oxidized to the quinone species by Fe 3+, contributing to fluorescence response to Fe 3+ . Thus, the N-CDs as fluorescence probes allowed the detection of Fe 3+ under acidic conditions, which has been verified in this work.